The Influence of Product Quality, Promotion, and Customer Satisfaction on Consumer Loyalty at PT Divo Kreasi Indonesia: The Influence of Product Quality, Promotion, and Customer Satisfaction on Consumer Loyalty at PT Divo Kreasi Indonesia - Purnama Yanti Purba; Maria Magdalena Sitorus; Marsella Chandra; Riris Butet Roy Marsela Limbong (Jurnal Mantik, 2020)
The purpose of this study is to examine the effect of Product Quality, Promotion, and Customer Satisfaction on Consumer Loyalty at PT Divo Kreasi Indonesia. The phenomenon of an increase in the number of consumer complaints, the less attractive promotions offered, and the inaccuracy of service completion are the background of this research. The sampling method used was simple random sampling. The result of the research is Product Quality, Promotion, and Consumer Satisfaction simultaneously have a positive and significant effect on Consumer Loyalty at PT Divo Kreasi Indonesia. Product quality, promotion, and customer satisfaction partially have a positive and significant effect on consumer loyalty at PT Divo Kreasi Indonesia.